Pengaruh Pengawasan, Kepemimpinan Dan Motivasi Kerja Terhadap Disiplin Kerja Pada Pegawai Kantor Dinas Ketahanan Pangan Dan Peternakan Provinsi Sumatera Utara - Nining Yustina; Zulaspan Tupti (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to determine and analyze the effect of supervision, leadership and work motivation on the work discipline of the Office of Food Security and Animal Husbandry Office of North Sumatra Province. The approach used in this study is an associative approach. The population in this study were all employees of the Office of Food Security and Animal Husbandry of North Sumatra Province. The sample in this study used the slovin formula, totaling 68 employees of the Office of Food Security and Animal Husbandry of North Sumatra Province. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) software program version 24.00. The results of this study prove that supervision, leadership and work motivation have a significant effect on work discipline for employees of the Office of Food Security and Animal Husbandry of North Sumatra Province.